The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1039/d0ra01705a
|View full text |Cite
|
Sign up to set email alerts
|

KOH activation of coal-derived microporous carbons for oxygen reduction and supercapacitors

Abstract: Porous carbons (PCs) with high specific surface areas were prepared using natural coal as precursor coupled with KOH activation, showing great potential as electrode materials for oxygen reduction and supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Recently, Wang et al reported the use of carboxylated coal-tar pitch with a poly­(acrylic acid) functional group as a precursor material for the synthesis of hierarchical porous carbon with a large surface area of 1295 m 2 g –1 to use as an electrode in a supercapacitor . Similarly, Guo et al also reported a series of porous carbons (PCs) from natural coal with a ultralarge specific surface area of 2092 m 2 g –1 followed by KOH chemical activation. Huang et al produced hierarchical porous carbons (HPCs) utilized for a supercapacitor electrode (specific capacitance 201 F g –1 ) from coal-derived humic acid (HA) by a facile KOH activation process.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Sup...mentioning
confidence: 99%
“…Recently, Wang et al reported the use of carboxylated coal-tar pitch with a poly­(acrylic acid) functional group as a precursor material for the synthesis of hierarchical porous carbon with a large surface area of 1295 m 2 g –1 to use as an electrode in a supercapacitor . Similarly, Guo et al also reported a series of porous carbons (PCs) from natural coal with a ultralarge specific surface area of 2092 m 2 g –1 followed by KOH chemical activation. Huang et al produced hierarchical porous carbons (HPCs) utilized for a supercapacitor electrode (specific capacitance 201 F g –1 ) from coal-derived humic acid (HA) by a facile KOH activation process.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Sup...mentioning
confidence: 99%
“…In such a scenario, the so-called unconventional energies should be used to meet energy requirements. 1 , 2 The one of the drawback is that there is no sustainable storage source to store such energies. Supercapacitors and batteries are a potential source of energies for practical use, while principle energy sources can be exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…In the developing modern era, the world is facing great hardships as fuel prices continue to rise, air pollution continues to rise, and fossil fuels become inadequate. In such a scenario, the so-called unconventional energies should be used to meet energy requirements. , The one of the drawback is that there is no sustainable storage source to store such energies. Supercapacitors and batteries are a potential source of energies for practical use, while principle energy sources can be exhausted. , Recently, supercapacitors have attracted a lot of interest due to their physicochemical characteristics because of double-layer capacitor (EDLC) or pseudocapacitor charge-storage mechanisms. , Pseudocapacitors are having high storage and on the other hand having low cyclic rate, whereas EDLC materials as carbon-based electrode materials exhibit excellent cyclability. Nanomaterials are widely used to provide alternative energy sources to eco-friendly fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Microporous carbon (MC) was synthesized according to previous literature. 30 , 31 First, bulky coals were broken and ground into powder in a mortar with a pestle. Two grams coal powder and 8 g KOH were placed in a mortar.…”
Section: Methodsmentioning
confidence: 99%